2018
DOI: 10.1002/lom3.10273
|View full text |Cite
|
Sign up to set email alerts
|

Methodological review and meta‐analysis of dilution assays for estimates of virus‐ and grazer‐mediated phytoplankton mortality

Abstract: This manuscript reviews methodological differences among modified dilution assay studies used to partition phytoplankton mortality into virus‐ and grazer‐mediated fractions, and discusses their implications. A meta‐analysis is also described, based on virus‐ and grazer‐mediated mortality and instantaneous growth rates extracted from these studies. As the α value used to assess the significance of these rates was not consistent across studies, metadata was re‐analyzed (i.e., rates were re‐calculated) using thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 50 publications
(126 reference statements)
1
13
0
Order By: Relevance
“…Although the 2-point approach used here has been demonstrated as a valid alternative to a dilution series for estimating grazing rates (Chen, 2015;Morison and Menden-Deuer, 2017), such an approach for viral dilutions remains to be assessed. As demonstrated in a recent meta-analysis, the modified dilution method suffers from a weak statistical power, even when multiple dilutions are used (Staniewski and Short, 2018). Despite these caveats, the calculated accumulation rates presented here matched well with the rates observed in situ, suggesting that viral lysis negligibly contributed to overall phytoplankton mortality.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Although the 2-point approach used here has been demonstrated as a valid alternative to a dilution series for estimating grazing rates (Chen, 2015;Morison and Menden-Deuer, 2017), such an approach for viral dilutions remains to be assessed. As demonstrated in a recent meta-analysis, the modified dilution method suffers from a weak statistical power, even when multiple dilutions are used (Staniewski and Short, 2018). Despite these caveats, the calculated accumulation rates presented here matched well with the rates observed in situ, suggesting that viral lysis negligibly contributed to overall phytoplankton mortality.…”
Section: Discussionsupporting
confidence: 66%
“…To estimate virus-induced mortality, microzooplankton grazing, and phytoplankton growth rates, we used a "modified dilution assay" (Evans et al, 2003;Kimmance and Brussaard, 2010;Staniewski and Short, 2018) using the 2-point method (Worden and Binder, 2003;Chen, 2015;Morison and Menden-Deuer, 2017) in a total of 11 experiments conducted at the station ( Table 1). Water for the experiments was collected from the surface (5 m) using the CTD rosette sampler.…”
Section: Incubation Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incubation period used in our dilutions may have been too short to capture viral infection, as often the viral lytic cycle can exceed 24 h (Evans et al, 2003;Jacquet et al, 2005). Lastly, recent meta-analysis revealed that over half of viral-induced mortality rates measured via the modified dilution approach were minimal (−0.1-0.1 day −1 ), which suggests that typical dilution assays may lack the sensitivity needed to detect viral mortality (Staniewski and Short, 2018). Other sources may have contributed to phytoplankton mortality in the estuary, such as consumption by mesozooplankton or benthic invertebrates (e.g., bivalves), though both processes were not measurable via dilution incubations and typically account for less consumption of primary production compared to microzooplankton (Cloern et al, 2014;Steinberg and Landry, 2017).…”
Section: Drivers Of Observed Ratesmentioning
confidence: 99%
“…viral lysis of phytoplankton or predation by un-modeled higher predators). However, grazing mortality is explicitly modeled in NEMURO and viral mortality is generally not a substantial loss term for bulk phytoplankton (Brum et al, 2014;Staniewski and Short, 2018). Quadratic mortality was retained for PZ, to account for predation pressure of un-modeled planktivorous fish.…”
Section: Modifications To the Original Biogeochemical Modelmentioning
confidence: 99%